EXCHANGE RATE, GDP, AND INTEREST RATE AS DRIVERS OF IT EXPORTS IN INDIA: A REGRESSION-BASED STUDY - Santosh. N; M. Muniraju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores what drives India’s IT exports, focusing on how exchange rates, economic growth, and interest rates play a role. Using data from 2012 to 2022, daily fluctuations in the Indian rupee-to-dollar exchange rate were averaged annually to capture trends, while yearly IT export figures (in ₹ crore), GDP changes, and interest rates were sourced from official reports. Over the ten-year period, IT exports averaged ₹710,212 crore, though this varied widely by year. The exchange rate between the Indian rupee and US dollar also shifted considerably, averaging 65.74 with noticeable fluctuations. Economic growth, measured by GDP, saw ups and downs—even dipping into negative territory during tough years—while interest rates ranged from historic lows to nearly 8%. The data shows that currency rates have a major impact on IT exports. A stronger rupee against the dollar exhibited a strong correlation with increased export income, accounting for nearly 92% of the observed fluctuations. In contrast, GDP changes and interest rates had little direct influence when considered independently. However, when paired with exchange rates, interest rates became relevant, suggesting combined effects on export performance. While some overlap between variables was noted, the models remained reliable. These findings highlight the outsized influence of currency dynamics on India’s IT sector. For businesses, managing exchange rate risks is critical to maintaining stability. For policymakers, fostering a predictable currency environment could help sustain India’s competitiveness in global IT markets.